Teacher morale and teaching performance of secondary school teachers of four selected Benedictine schools - Caneo, Virginia O. (Animo Repository, 1993)
The study which used the descriptive-correlational method determined the relationship between morale and teaching performance of secondary school teachers of four selected Benedictine schools. Two instruments were employed in this study to attain its objectives. These are the Staff Morale Questionnaire by Kevin Smith and was adapted for Philippine setting by Dr. Nenita Mercado, which purports to determine the level of morale of the teacher respondents and the Teacher Behavior Inventory (TBI) by Kendall Tang, an instrument designed primarily to determine how often the teacher performs certain behaviors in five areas. The respondents of the study consisted of 60 secondary school teachers of the four Benedictine Schools, whose ages range from 21 to 52.For the treatment of data, each item and area in the two instruments were expressed in terms of frequency, mean, and standard deviation. Multiple correlation through stepwise regression was used to determine the relationship between teacher morale and teaching performance. The findings of the study revealed that the teachers in the four respondent schools were generally effective in their teaching performance. Teacher respondents scored high on both levels of morale and teaching performance but these variables are not significantly related to one another. It also revealed that there was no relationship between morale and the personal variables, and no relationship between teaching performance and the personal variables. Based on the findings recommendations for dissemination of the study especially to the teacher respondents and to the school principals were made. It also recommends further studies covering other correlates and predictors of teacher morale and performance.